Design of Smart Trash Can Using Fuzzy Logic Algorithm Based on Arduino - Azmi, Fadhillah; William, William; Salim, Kevin Kristanto; Hartanto, Tommy Tiara; Tham, Felix (JITE (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING), 2019)
Smart trash cans use a proximity sensor (ultrasonic) to detect the height of the trash, the PIR (Passive Infra Red) sensor to detect human presence and Arduino as the data processing center. This trash can also has an LED that functions as an indicator and the buzzer functions as an alarm when the trash can is full. If the garbage reaches half of the trash, the LED will turn yellow, if the garbage reaches a height of 4cm from the trash lid, then the LED will turn red and so the trash can will be locked even though the PIR sensor detects humans. Buzzer will live to attract the attention of cleaning officers to dispose of trash. To dispose of garbage, the clerk needs to shift the open and close trash button so that the lid will open. The author hopes that this smart trash can can increase public awareness to dispose of garbage in its place. The results of study show that PIR sensors work by well in detecting the presence of humans and ultrasonic sensors in detecting the height of garbage are not accurate, so that if the trash if the trash can is empty, sometimes the garbage is minus, whereasif the garbage is < 3.5 cm, the sensor fails detect it.